Analisis Identitas Budaya Pakaian Adat Jambi Suku Melayu - Ainun Nisa Rosiana; Syairul Bahar; Dinda Nur Azizah; Dzaki Abiansyah Putra; Lutfiah Rustianti; Rabella Azzahra; Syifa Almanda Ru’yat; Farkhan Abdurochim Alfarauq (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research aims to analyze the making and use of Jambi traditional clothing with an ethnographic approach, in order to reveal cultural values, symbolism, and its role in the identity of the Jambi Malay community. The method used in this research is a qualitative approach, where data collection techniques include in-depth interviews, direct observation, and document analysis. Interviews were conducted with informants who have in-depth knowledge of Jambi traditional clothing, while observation involved observing the making process, design, and use of the clothing in traditional ceremonies. The results showed that Jambi traditional clothing, such as Baju Kurung Tanggung, reflects the richness of local culture through designs that are full of philosophy. The symbolic colors used, such as red, gold and green, symbolize courage, nobility and fertility. In addition, these traditional garments also serve as symbols of social status and cultural identity, especially in the context of weddings and traditional ceremonies.